Inhibition of Protein Synthesis by Y Box-Binding Protein 1 Blocks Oncogenic Cell Transformation - Bader, Andreas G. (American Society for Microbiology, 2005)
The multifunctional Y box-binding protein 1 (YB-1) is transcriptionally repressed by the oncogenic phosphoinositide 3-kinase (PI3K) pathway (with P3K as an oncogenic homolog of the catalytic subunit) and, when reexpressed with the retroviral vector RCAS, interferes with P3K- and Akt-induced transformation of chicken embryo fibroblasts. Retrovirally expressed YB-1 binds to the cap of mRNAs and inhibits cap-dependent and cap-independent translation. To determine the requirements for the inhibitory role of YB-1 in P3K-induced transformation, we conducted a mutational analysis, measuring YB-1-induced interference with transformation, subcellular localization, cap binding, mRNA binding, homodimerization, and inhibition of translation. The results show that (i) interference with transformation requires RNA binding and a C-terminal domain that is distinct from the cytoplasmic retention domain, (ii) interference with transformation is tightly correlated with inhibition of translation, and (iii) masking of mRNAs by YB-1 is not sufficient to block transformation or to inhibit translation. We identified a noncanonical nuclear localization signal (NLS) in the C-terminal half of YB-1. A mutant lacking the NLS retains its ability to interfere with transformation, indicating that a nuclear function is not required. These results suggest that YB-1 interferes with P3K-induced transformation by a specific inhibition of translation through its RNA-binding domain and a region in the C-terminal domain. Potential functions of the C-terminal region are discussed.